2024
DOI: 10.1038/s41598-024-51271-9
|View full text |Cite
|
Sign up to set email alerts
|

In situ and bio-green synthesis of silver nanoparticles immobilized on zeolite as a recyclable catalyst for the degradation of OPDs

Fujiang Zhou,
Danfeng He,
Guojian Ren
et al.

Abstract: In this study, silver nanoparticles (Ag-NPs) were synthesized using a green and biologically inspired approach by utilizing reducing compounds from Thyme plant leaves. Zeolite was used to immobilize the synthesized Ag-NPs (Ag@Z). The modified Zeolite served as a catalyst for the reduction reaction of various organic pollutant dyes (OPDs) including 4-nitrophenol (4-NP), 4-nitroaniline (4-NA), methylene blue (MB), and methyl orange (MO) with sodium borohydride. The degradation of OPDs was monitored by measuring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Comparison of Entries 6 and 7 reveals that while Ag 3 PO 4 has limited capability in degrading COPs, the addition of NaBH 4 greatly enhances reaction efficiency and degradation rate. Sodium borohydride is thought to induce the reduction of silver ions and formation of Ag nanoparticles, enabling them to effectively catalyze the degradation of the desired COP compounds 9 , 64 . Considering our primary objective of conducting environmentally friendly processes and degrading environmental pollutants, we have overlooked application of Ag-MIL-101 composite as catalyst for the COP degradation reaction in the presence of NaBH 4 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Comparison of Entries 6 and 7 reveals that while Ag 3 PO 4 has limited capability in degrading COPs, the addition of NaBH 4 greatly enhances reaction efficiency and degradation rate. Sodium borohydride is thought to induce the reduction of silver ions and formation of Ag nanoparticles, enabling them to effectively catalyze the degradation of the desired COP compounds 9 , 64 . Considering our primary objective of conducting environmentally friendly processes and degrading environmental pollutants, we have overlooked application of Ag-MIL-101 composite as catalyst for the COP degradation reaction in the presence of NaBH 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Water treatment involves physicochemical and biological methods 8 , 9 . Advanced technologies like adsorption, advanced oxidation (by efficient materials such as peroxodisulfate (PDS), peroxomonosulfate (PMS) or hydrogen peroxide (H 2 O 2 )), flocculation, and filtration, along with innovative approaches like microbiological and electro-catalytic methods, have gained attention for water treatment 10 15 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is due to the reaction time between the synthesized catalyst and MO dye affecting the saturation state of the Bi/HAp-rGO surface. With the increase of reaction time, MO molecules will interact more with the reaction sites on the catalyst surface, resulting in increased decolorization efficiency of MO (Al-Ansari et al 2024 ; Zhou et al 2024 ). It was observed that the maximum decolorization efficiency of MO reached its maximum in about 3 min and did not show a significant increase at later levels.…”
Section: Resultsmentioning
confidence: 99%